Research progress on natural plant metabolites targeting apoptosis for endometriosis prevention and treatment: a systematic review - Yu, Yang; Zhu, Yufei; Gao, Mengyao; Wang, Yu; Li, Shiying; Gou, Ying (Frontiers in Pharmacology, 2025)
Endometriosis (EMs) is a prevalent benign gynecological disorder characterized by dysmenorrhea and infertility, significantly impacting women’s health and quality of life. Currently, the pathogenesis of EMs remains incompletely elucidated. There are various side effects of drug treatment, while surgical interventions involve a certain degree of tissue trauma. Therefore, novel therapeutic drugs and clinical strategies should be developed. Apoptosis, a programmed cell death pathway, maintains tissue homeostasis, and its dysregulation is linked to various diseases and pathological complexities. Accumulating evidence suggests that abnormal apoptosis is intricately linked to the development and progression of EMs and that targeted promotion of cell apoptosis may contribute to the prevention and treatment of EMs. Natural metabolites, with their biological properties such as multipathway and multitarget effects, exhibit unique advantages in treating EMs, possibly by regulating apoptosis. This paper reviews the relationship between apoptosis and EMs. It systematically summarizes the latest progress of natural metabolites in treating EMS by regulating apoptosis, offering an innovative strategy for treating EMs.